Factors affecting the lending rate: a case of banking sector in Malaysia / Nurain Fatimah Azmi - Azmi, Nurain Fatimah (Faculty of Business Management, 2018)
The variation of lending rate of the commercial banks in Malaysia has been the main issue when the customers are considering about having a loan. There were factors that influencing the determination of lending rate for commercial banks in Malaysia. The main objective of this study is to determine the relationship between inner factors and lending rate of commercial banks in Malaysia. This study use panel data method. The period of the study is for 3 years specifically for the year of 2015 to 2017. This study is conducted by using annual data basis for 10 commercial banks in Malaysia. The sample data were sourced from annual financial report for each of the commercial banks. Commercial banks which will be the sample in this study is Affin Bank Bhd, Alliance Bank Malaysia Bhd, AmBank(M) Bhd, Citibank Bhd, CIMB Bank Bhd, Hong Leong Bank Bhd, HSBC Bank Malaysia Bhd, OCBC Bank (Malaysia) Bhd, Public Bank Bhd and RHB Bank Bhd. In this study, lending rate is the dependent variable. To measure the relationship towards determination of lending rate, capital adequacy, management efficiency, liquidity, loan to asset and deposit to asset ratio has been selected as the independent variables. From this study, loan to asset and deposit to asset ratio are expected to have the negative significant relationship with lending rate which indicates that both of the ratio have an inverse relationship with lending rate. Liquidity ratio are expected to have a positive significant relationship towards lending rate.